RiGOR: a prospective observational study comparing the effectiveness of treatment strategies for open-angle glaucoma. (January 2016) - Coleman, Anne L; Lum, Flora C; Velentgas, Priscilla; Campion, Daniel; Su, Zhaohui; Gliklich, Richard E; ,
Aims: The RigOR study was designed to assess comparative effectiveness of medications, laser trabeculoplasty and incisional surgery in patients with open-angle glaucoma (OAG) in the community initiating a new or additional course of therapy as judged necessary by their ophthalmologist. This paper focuses specifically on demographic and clinical characteristics of OAG patients at enrollment.Patients & methods: A total of 2597 with OAG already on medical therapy were enrolled from 45 community and academic practices throughout the USA.Results: Overall, 784 (30%) patients were treated with laser surgery, 436 with other surgical procedures (17%), and 1377 with additional medication (53%). Patients had mild (35%) or moderate (31%) glaucoma, with 28% with severe glaucoma.Conclusion: The RiGOR study enrolled a diverse population and will provide valuable information regarding visual function and treatment patterns among different racial/ethnic populations. African–American and Hispanic patients entered the study with poorer visual acuity and more severe glaucoma.